376 Knowledge and use of child mental well-being services during the Covid-19 pandemic. (17th August 2022) - Bramer, Solange; Harrington, Emma; Knight, Katie; Fuller, Fionnghuala
Abstract : Aims: The UK implemented several restrictions and lockdowns in response to the Covid-19 pandemic which significantly affected children's lives, despite children being at lower risk of severe disease from Covid-19. 1 A small number of studies have evaluated the pandemic's impact on the mental health of children. Their findings show that the majority of children with pre-existing mental health conditions report a worsening of their mental health during the pandemic. Overall, child mental health worsened when restrictions were in place, and improved as restrictions eased. 2 There have been long-standing concerns over inadequate mental health service provision for children in the UK. This study aimed to analyse children and caregivers' knowledge and use of child mental well-being services during the Covid-19 pandemic. Methods: A survey evaluating knowledge and use of services that support mental well-being was distributed to caregivers and children (if aged >5 years) attending a paediatric emergency department in April-May 2021. Responses were analysed according to gender and age (0-5, 5-11, >12 years old). This study included both quantitative data and free-text responses. This was a service evaluation project to identify how services aimed at child well-being were used during the pandemic and how these could be improved. Results: 193 children and 308 adults participated in the study, leading to a response rate of 98%. The majority of respondents felt they knew who to turn to for emotional support, despite two in five older girls not knowing where to access support. 45% of caregivers were worried about accessing services during the pandemic. Family was the most common source of support for children of all ages, whilst less than 10% would seek advice from online sources (i.e. MIND). Two thirds of caregivers would seek advice from their GP compared to less than 5% of older children. 10% of younger children and 17.5% of older children reported not wanting to talk to anyone about their mental well-being. 95 participants responded to the optional free-text question about the general impact of the pandemic. Common themes from these responses are summarised in table 1 . Only two children and three caregivers described positive aspects of the pandemic. Conclusion: Worsening mental health and barriers to accessing services designed to support mental well-being have compounded long-standing concerns of inadequate service provision. The proportion of girls unaware of sources of support and of children overall unwilling to seek help for their mental well-being is worrying. Services need to adapt to meet gender and age-specific needs. Dedicated training for healthcare workers may enable signposting to appropriate services. The minor use of online services could be harnessed to reduce the burden on overstretched services like general practice and emergency departments. These findings demonstrate the importance of involving young people in designing mental health policy and educating children and caregivers about the types of mental well-being support available. References: Waite et al. How did the mental health symptoms of children and adolescents change over early lockdown during the COVID-19 pandemic in the UK? Young Minds. Coronavirus: Impact on young people with mental health needs.